(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the sensitivity and specificity of visual inspection of the cervix with 5% acetic acid to Pap smear by using the colposcopically directed biopsy as Gold Standard in the diagnosis of cervical cancer and assessing the concordance of VIA with colposcopy. Study Design: Cross sectional validation study Place and Duration of Study: This study was conducted at the Gynaecology and Obstetrics Department of Holy Family Hospital Unit-1 from1st Nov.2014to 30th April 2015. Materials and Methods: Females fulfilling the inclusion criteria were selected in the study from outpatient department. Bias was controlled by strictly following the inclusion and exclusion criteria. Results: The sensitivity of VIA was 91.67% and of Pap smear was 81.81% . Corresponding specificities were 97.44% and 96.20%. The PPV of VIA was 84.62% versus 75.00% for Pap smear. The NPV of VIA was 98.70% versus 97.44% for cytology. Overall VIA demonstrated an accuracy of 96.67% as compared to 97.77% for cytology. Conclusion: In woman undergoing screening for Pre-invasive disease of Cervix, visual inspection using 5% acetic acid was found to be more sensitive and has a similar accuracy as compared to Pap smear.